2022
DOI: 10.1039/d1qi00226k
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-dependent textural properties of defective UiO-66 after acidic and basic treatment

Abstract: We report the effect of inorganic and organic acids and bases, in combination with different solvents, on the crystallinity and porosity of defective UiO-66 MOFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This excellent resistance to strong acids and bases is rare in MOFs materials, which is almost comparable to that of the star MOF material UIO-66. 40 From the crystal structure analysis, the superior stability of SrCu (HC 3 N 3 O 3 ) 2 comes from three parts: high ratio of coordination sites in organic ligand, specific coordination of strong acid with a strong base and weak acid with a weak base, and double independent completion coordination network. In summary, the ultra-stable MOFs of SrCu(HC 3 N 3 O 3 ) 2 have more potential for practical applications.…”
Section: Stability Studiesmentioning
confidence: 99%
“…This excellent resistance to strong acids and bases is rare in MOFs materials, which is almost comparable to that of the star MOF material UIO-66. 40 From the crystal structure analysis, the superior stability of SrCu (HC 3 N 3 O 3 ) 2 comes from three parts: high ratio of coordination sites in organic ligand, specific coordination of strong acid with a strong base and weak acid with a weak base, and double independent completion coordination network. In summary, the ultra-stable MOFs of SrCu(HC 3 N 3 O 3 ) 2 have more potential for practical applications.…”
Section: Stability Studiesmentioning
confidence: 99%
“…36,37,[43][44][45][46][47] Many of the stability studies in aqueous media that were presented in the literature are based on a post-exposure analysis of the corresponding solids using powder X-ray diffraction (XRPD), gas adsorption, scanning electron microscopy (SEM), infrared spectroscopy (FTIR), or their combination with computational methods. 26,32,45,46,[48][49][50][51][52][53] For example, when MOFs' stability is inferred from XRPD patterns before and after the treatment, while ignoring the mass balance, presence of an amorphous phase, and changes in the chemical composition, erroneous conclusions can be drawn. In our recent studies, we have demonstrated that the structure of UiO-66, a Zr-based MOF considered one of the most stable MOFs, is compromised already at neutral pH or in the presence of commonly used buffers, such as TRIS or phosphate-buffered saline.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several reports on the generation of defect sties in UiO-66 by using acid modulators, the obtained defect sites are not effective for As­(III) adsorption. Base treatments have been accounted for defect engineering in MOFs. Weak organic bases and N-type bases have been studied due to the evasion of MOF deconstruction. The use of triethylamine in MeOH solution has been reported for the generation of defect sites, which are the open sites for guest molecules binding on Zr-based MOFs. , To the best of our knowledge, the hydroxylation of MOFs using hydroxy bases to enhance their adsorption performances has not been demonstrated so far.…”
Section: Introductionmentioning
confidence: 99%